PENYUSUNAN BAHAN PEMBELAJARAN KOMPILASI BAGI GURU-GURU SMK DI KECAMATAN MUARA GEMBONG KABUPATEN BEKASI, JAWA BARAT - Rusmono; Wisnu Djatmiko (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2023)
Abstrac In general, vocational school teachers use existing learning modules, including modules developed by the Ministry of Education and Culture, and their implementation in educational units needs to be adjusted to the characteristics of students. Desa Pantai Sederhana, Muara Gembong District, Bekasi Regency, West Java, as a partner institution, has a problem, namely that the large number of private vocational school teachers who teach at vocational schools in Desa Pantai Sederhana are not yet accustomed to developing learning materials referring to the learning objectives and characteristics of the students in subjects for which he is responsible. If this condition continues to recur, it can be assumed that facilitating learning to improving performance for students is difficult to achieve, so it is necessary to train the abilities and skills of teachers in partner areas to be able to develop complex learning materials in accordance with learning objectives and characteristics of students. Implementation of community service in the form of